The Effect of Giving Five Finger Hypnosis and Hegu LI4 Point Acupressure on the Intensity of Dysmenorrhea in Adolescent Girls at Junior high school PGRI 2 Denpasar - Widiastini, Luh Putu; Mirah Yunita Udayani, Ni Putu (Jurnal Kesehatan Pasak Bumi Kalimantan, 2024)
Dysmenorrhea is abdominal pain felt during menstruation, where many young women experience decreased concentration in studying due to the dysmenorrhea they experience. The aim of this research is to determine the effect of administering Five Finger Hypnosis and Hegu LI4 Point Acupressure on the intensity of dysmenorrhea in adolescent girls. The design of this research was Quasi Experimental with a Non-Equivalent Control Group Design research design, with a sample of 40 class IX teenage girls who experienced dysmenorrhea at SMP PGRI 2 Denpasar. The sample was divided into two groups, namely the treatment group and the control group. Data were analyzed using Shapiro-Wilk to compare pretest and post-test results and Mann Whitney to compare the results of data analysis between the treatment group and the control group. From the results of data analysis in the treatment group and control group before being given Five Finger Hypnosis and Hegu LI 4 Point Acupressure, a p value of 0.299 was obtained, which means p > 0.05. After being given Five Finger Hypnosis and Hegu Point LI 4 Acupressure in the treatment group, the value of p = 0.000 was obtained, which means p < 0.05, so it can be concluded that there was an effect of giving Five Finger Hypnosis and Hegu Point LI 4 Acupressure on the intensity of dysmenorrhea pain in young women.